2020
DOI: 10.1186/s13256-020-02381-1
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromatosis type 1 associated with hypophosphatemic osteomalacia due to hypersecretion of fibroblast growth factor 23: a case report

Abstract: Background: Neurofibromatosis type 1 is characterized by multiple café au lait spots and cutaneous and plexiform neurofibromas, and is one of the most common autosomal dominant hereditary disorders caused by mutations of the neurofibromatosis type 1 tumor suppressor gene. Osteomalacia in neurofibromatosis type 1 is very rare and is characterized by later onset in adulthood. In humans, fibroblast growth factor 23, which is a causative factor of tumor-induced osteomalacia, is not only a paracrine and autocrine f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Information on 99 patients (70.2%) was collected in the secondary survey. Eleven patients were excluded from the analysis: one patient was counted twice, one patient had neurofibromatosis 1 associated with FGF23-related hypophosphatemic osteomalacia, (25,26) and nine patients did not meet the eligibility criteria regarding the time of the first visit to the hospital. As a result, 88 patients who were definite or clinically diagnosed with TIO were selected for the study.…”
Section: Resultsmentioning
confidence: 99%
“…Information on 99 patients (70.2%) was collected in the secondary survey. Eleven patients were excluded from the analysis: one patient was counted twice, one patient had neurofibromatosis 1 associated with FGF23-related hypophosphatemic osteomalacia, (25,26) and nine patients did not meet the eligibility criteria regarding the time of the first visit to the hospital. As a result, 88 patients who were definite or clinically diagnosed with TIO were selected for the study.…”
Section: Resultsmentioning
confidence: 99%
“…In the same study, micro-ct examination, also, demonstrated thinner and porous cortical bones with disorganized osteocyte dendrites that exhibited reduced strength in mechanical forces leading to spontaneous fractures [ 34 ]. This was supported by the clinical findings of increased circulating levels of FGF-23 in two patients with NF1 that appeared severe HO [ 23 , 25 ]. A possible explanation was that the increased serum concentration of FGF-23 inhibited renal reabsorption of phosphorus and decreased the production of 1,25--dihydroxyvitamin D leading to increased phosphate wasting and lower levels of phosphorus in the serum [ 34 ].…”
Section: Discussionmentioning
confidence: 63%
“…Multiple myelomas, hemangiopericytomas, osteosarcomas, chondroblastomas, chondrofibroid myxomas, malignant fibrous histiocytomas, giant cell tumors, and prostatic cancers are entities that were associated with adult-onset HO [ 20 , 21 ]. NF1 has been implicated with HO very rarely ( Table 1 ) [ 22 , 23 , 23 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Despite the fact, that the association between NF1 and HO was described by Gould in 1918, <50 cases have been referred in the international literature [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation